Social and demographic correlates of cardiovascular mortality in the Kassena-Nankana districts of Ghana: a verbal post-mortem analysis. (27th December 2021) - Oduro, Abraham R; Francke, Jordan; Ansah, Patrick; Jackson, Elizabeth F; Wak, George; Phillips, James F; Haykin, Leah A; Azongo, Daniel; Bawah, Ayaga A; Welaga, Paul; Hodgson, Abraham; Aborigo, Raymond; et al.
Abstract: Background: The burden of cardiovascular disease (CVD) in Ghana is rising, but details on its epidemiology are scarce. We sought to quantify mortality due to CVD in two districts in rural Ghana using verbal post-mortem (VPM) data. Methods: We conducted a proportional sub-hazards analysis of 10 232 deaths in the Kassena-Nankana East and West districts from 2005 to 2012, to determine adult mortality attributed to CVD over time. We stratified results by age, gender and socio-economic status (SES), and compared CVD mortality among SES and gender strata over time. A competing risk model estimated the cumulative effect of eliminating CVD from the area. Results: From 2005 to 2012, CVD mortality more than doubled overall, from 0.51 deaths for every 1000 person-years in 2005 to 1.08 per 1000 person-years in 2012. Mortality peaked in 2008 at 1.23 deaths per 1000 person-years. Increases were comparable in men (2.0) and women (2.3), but greater among the poorest residents (3.3) than the richest (1.3), and among persons aged 55–69 years (2.1) than those aged ≥70 years (1.8). By 2012, male and female CVD mortality was highest in middle-SES persons. We project that eliminating CVD would increase the number of individuals reaching age 73 years from 35% to 40%, adding 1.6 years of life expectancy. Conclusions: The burden of CVD on overall mortality in the Upper East Region is substantial and markedly increasing. CVD mortality has especially increased in lower-income persons and persons in middle age. Further initiatives for the surveillance and control of CVD in these vulnerable populations are needed.